Management and Financial Transparency Assistance to Build Public Trust in Madrasah Ibtidaiyah Muhammadiyah 3 Ngunut - Iman, Nurul; Rudianto; Jihan Nabila Zahara (Mangabdi: Journal of Community Engagement in Religion, Social, and Humanities, 2025)
Management and financial transparency are crucial aspects in realizing accountable governance within educational institutions and fostering public trust. This community service program aims to enhance financial management capacity at Madrasah Ibtidaiyah Muhammadiyah (MIM) 3 Ngunut Ponorogo, making it more transparent, structured, and aligned with the principles of good governance. The program was implemented through four interconnected stages: program socialization, a workshop on the Model of a School Trusted by the Community, a workshop on management and financial transparency, and intensive mentoring for transparency implementation. The qualitative data analyzed consisted of observation notes, documentation of financial records, questionnaire responses on public trust indicators, outputs from focus group discussions and workshops, and SWOT analysis matrices. SWOT analysis was utilized as an analytical tool to examine internal and external conditions related to financial transparency implementation and to formulate strategic follow-up actions. The program employed a qualitative approach using a Participatory Action Research (PAR) design, emphasizing collaborative problem identification, joint action, and reflective evaluation involving madrasah stakeholders. The results indicate improved administrators’ understanding of financial recording and reporting principles, increased awareness of the importance of public transparency, and a strong institutional commitment to developing a digital-based financial reporting system. Enhanced communication and stakeholder participation also contributed to strengthening public trust between the madrasah, parents, and the wider community. This program contributes to the development of a professional, participatory, and integrity-based governance model for Islamic elementary education institutions and supports the achievement of the Sustainable Development Goals (SDGs), particularly Goal 4 (Quality Education) and Goal 16 (Transparent and Accountable Institutions).